Coastal exposure assessment on Bonassola bay. (1st January 2019) - Mucerino, L.; Albarella, M.; Carpi, L.; Besio, G.; Benedetti, A.; Corradi, N.; Firpo, M.; Ferrari, M.
Abstract: This paper illustrates a novel coastal exposure assessment approach. The approach is based on the employment of the model chain WavewatchIII+XBeach, which is first used to draw a map showing the extent of the populated areas that are likely to be interested by flooding, and subsequently to establish the exposure of the area to specific events. The model chain is calibrated by comparing the simulated runup values of a storm with those obtained by processing on-field images recorded by a camera system. The approach herein presented allows to take into account the local coastal geomorphology features and hydrodynamics of the area so as to obtain locally accurate results. The information collected is usable by local beach managers in coastal management planning. The method is applied on Bonassola beach, which is a pocket beach located on the NW Mediterranean along the Eastern coast of Liguria, Italy. Weather and offshore waves data collected during the last 16 years were used. The application of this method has allowed to draw a map of the areas that are subject to flooding during storms and has correctly stated that three of the seven biggest storms in the last 16 years would eventually result into flooding of populated area. The study has also shown that the exposure of the study area to the storms is sensitive to the period and the direction of the waves. Highlights: Coastal exposure map allows to coastal managers to evaluate local risk level. Local scale application supplies more accuracy of storm impact. Model chain is operative tool to evaluate coastal hydrodynamic pattern. Camera system supply accurate runup excursion values on investigated area. Flooding risk is related to coastal geomorphology and grain size distribution.